Wired to be connected? Links between mobile technology engagement, intertemporal preference and frontostriatal white matter connectivity. Issue 4 (25th April 2019) - Wilmer, Henry H; Hampton, William H; Olino, Thomas M; Olson, Ingrid R; Chein, Jason M
Abstract: Youth around the world are increasingly dependent on social media and mobile smartphones. This phenomenon has generated considerable speculation regarding the impacts of extensive technology engagement on cognitive development and how these habits might be 'rewiring' the brains of those growing up in a heavily digital era. In an initial study conducted with healthy young adults, we utilized behavioral and self-report measures to demonstrate associations between smartphone usage habits (assessed both subjectively and objectively) and individual differences in intertemporal preference and reward sensitivity. In a follow-up neuroimaging study, we used probabilistic tractography of diffusion-weighted images to determine how these individual difference characteristics might relate to variation in white matter connectivity, focusing on two dissociable pathways—one connecting the ventral striatum (vSTR) with the ventromedial prefrontal cortex (vmPFC) and the other connecting the vSTR with the dorsolateral prefrontal cortex (dlPFC). Regression analyses revealed opposing patterns of association, with stronger vSTR–vmPFC connectivity corresponding to increased mobile technology engagement but stronger vSTR–dlPFC connectivity corresponding to decreased engagement. Taken together, the results of these two studies provide important foundational evidence for both neural and cognitive factors that can be linked to how individuals engage with mobile technology.